Analysis of diagnostics, therapy and outcome of patients with traumatic atlanto-occipital dislocation - Jung, Matthias; Hörnig, Lukas; Stübs, Michael M. A.; Grützner, Paul Alfred; Kreinest, Michael (The spine journal, 2021)
BACKGROUND CONTEXT - Patients’ outcome following traumatic atlanto-occipital dislocation (AOD) has been poor. In recent years, an increasing number of patients surviving the initial trauma are admitted to hospital. In order to further improve the management of these patients, the knowledge of diagnostics and therapy as well as possible complications should be increased. - PURRPOSE - The aim of this study was to evaluate diagnostic parameters, therapy, early complications and outcome of patients with traumatic AOD. - STUDY DESIGN - Monocentric retrospective cohort study. - PATIENT SAMPLE - A total of 12 patients were included in this study. - OUTCOME MEASURES - The main outcome measure was functional patient outcome. Furthermore, radiographic and treatment data were analyzed. - METHODS - All patients suffering from traumatic AOD within an 8-year time period were included. Demographic data, radiological diagnostic parameters (condylar sum, basion dens interval, basion axis interval, power´s ratio, x-line method), as well as treatment data and complications of every patient were analyzed. Radiological parameters were compared with each other. Outcome was analyzed by a follow up examination. - RESULTS - The accident mechanisms were motor vehicle accidents (MVA), fall from high and low height. Basion dens interval, basion axis interval, power's ratio and x-line method were not reliable in identifying traumatic AOD (only up to 33% of the patients were identified). Twelve patients could be reviewed. Three patients were treated with surgery, five patients were treated nonsurgically. Four patients died before surgical therapy. All seven surviving patients (survival rate: 58.3%) were re-examined (mean follow-up time: 6.7 months). All patients had a GCS of 15. Three surviving patients suffered from persisting neurological deficits. - CONCLUSIONS - The most reliable way to diagnose AOD in Computer Topography is using the condylar sum. Surgical and nonsurgical measures can be employed with reasonable outcomes. Patient specific injury burden and clinical presentation should be taken into account when making treatment decisions for AOD.
Gesehen am 18.11.2021